Ethical Relation between Physicians and Pharmaceutical Industries in the Perspectives of Bangladesh (Bangladesh Journal of Bioethics, 2015)
Relation between physicians and pharmaceutical industry is required for the benefit of the patient. But it may turn into business and overthrow the patients benefit. The relation might be in question at present and in future. Several questions are flowing in Bangladesh. To solve these queries we have explored the situation in developed and developing countries. The physicians and associations of pharmaceutical industries developed several ethical guidelines in those countries. They have addressed the long lasting issues on gift provided to physician, cash back, sample, industry sponsored scientific meetings, research and hospitality. There are huge restrictions to ensure the right of the patients e.g. limitation of inexpensive gift by the pharmaceuticals, avoiding expensive medicine instead of equally effective low priced medicine. We are lacking behind to protect the patient right properly: regulation, adherence to existing guide line, lack of guidance from statutory bodies. The current scenario is far behind the right of patient. In Bangladesh it is not yet addressed either by professionals or by pharmaceutical associations. It is the immediate need to construct a guide line for physicians and pharmaceutical industry of Bangladesh.Bangladesh Journal of Bioethics 2015 Vol.6 (1):1-5